Şeybânî Hanlığı’nda hukuk sistemi : şer‘î hukuk ve örfî hukuk (1500-1599) - Khamıdzhanova, Shokhsanam (My University, 2024)
Şeybânîler; Mâverâünnehir ve Horasan’da Timurlulardan sonra bir asır boyunca hüküm süren ve ismini Cengiz Han’ın büyük oğlu Cuci’nin Şeybân adındaki oğlundan alan bir İslâm hanedanıdır. Bu çalışma, Mâverâünnehir bölgesinde geç dönemde Hanefî mezhebinin konumu, fıkhî yaklaşımlar, gelişmeler ve uygulamaları tespit etme amacıyla 16. yüzyılda Şeybânî Hanlığında uygulanan ve bir taraftan özel hukuk alanlarına hakim olan “şer‘î hukuk”un izlerini diğer taraftan konunun bütüncül anlaşılması açısından kamu hukukunu düzenleyen Cengiz yasası ve Türk halklarının âdetlerinden kaynaklanan örfî hukuk uygulamalarını ele almaktadır.

The Shaybānids were one of the regional khanates that ruled in Māwarannahr and Khorasan for a century after the Timurids, and were an Islamic dynasty that traces its origins back to the son of Genghis Khan's eldest son, Juchi, named Shaybān. This study aims to evaluate the impressions of the Shaybānid dynasty's sixteenth-century “sharī'ah law” in the fields of private law in order to identify the practical status of Hanafism in these regions, jurisprudential developments, innovations and practices in the late period of Māwarannahr. For a holistic understanding of the subject, the general characteristics of customary law and Sharia law, which originated from the Genghis law and Turkic customs, are evaluated together.
Keywords: Customary Law; Hanafi; Hanefîlik; History; Islamic law; İslam hukuku; Örfî hukuk; Sharia Law; Şer‘î hukuk; Şeybânîler; Tarih; Yasa; Yasa Shaybanids